Biosynthesis of riboflavin in Bacillus subtilis: origin of the four-carbon moiety. - Le Van, Q (1985)
We studied the incorporation of [1-13C]ribose and [1,3-13C2]glycerol into the riboflavin precursor 6,7-dimethyl-8-ribityllumazine, using a riboflavin-deficient mutant of Bacillus subtilis. The formation of the pyrazine ring requires the addition of a four-carbon moiety to a pyrimidine precursor. The results show that C-6 alpha, C-6, C-7, and C-7 alpha of 6,7-dimethyl-8-ribityllumazine were biosynthetically equivalent to C-1, C-2, C-3, and C-5 of a pentose phosphate. C-4 of the pentose precursor was lost through an intramolecular skeletal rearrangement. Thus, the last steps in the biosynthesis of 6,7-dimethyl-8-ribityllumazine apparently involve the same mechanism in bacteria as in fungi.